VD_FINDINFO Jug / 2017 / 37 vom 22. März 2016 - VD Tribunal cantonal (2016)
CONTRAINTE SEXUELLE, ACTE D'ORDRE SEXUEL SUR UN INCAPABLE DE DISCERNEMENT | 189 CP, 191 CP, 49 al. 1 CP, 51 CP, 25 DPMin, 3 DPMin, 135 al. 4 CPP (CH)